2018
DOI: 10.1093/mnras/sty2108
|View full text |Cite|
|
Sign up to set email alerts
|

Multiplicity of disc-bearing stars in Upper Scorpius and Upper Centaurus-Lupus

Abstract: We present observations of disc-bearing stars in Upper Scorpius (US) and Upper Centaurus-Lupus (UCL) with moderate resolution spectroscopy in order to determine the influence of multiplicity on disc persistence after ∼ 5−20 Myr. Discs were identified using infra-red (IR) excess from the Wide-field Infra-red Survey Explorer (WISE) survey. Our survey consists of 55 US members and 28 UCL members, using spatial and kinematic information to assign a probability of membership. Spectra are gathered from the ANU 2.3m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 82 publications
3
16
0
Order By: Relevance
“…Overall, the influence of multiplicity on the disc lifetime has yet to be determined. Shorter circumstellar and circumbinary disc lifetimes are implied by the low disc frequency around binaries of separation a < 40 AU (Cieza et al 2009;Duchêne 2010;Kraus et al 2011); however, Kuruwita et al (2018) find that overall, the lifetime of discs in binaries may not vary significantly compared to disc lifetimes around single stars.…”
Section: Introductionmentioning
confidence: 61%
“…Overall, the influence of multiplicity on the disc lifetime has yet to be determined. Shorter circumstellar and circumbinary disc lifetimes are implied by the low disc frequency around binaries of separation a < 40 AU (Cieza et al 2009;Duchêne 2010;Kraus et al 2011); however, Kuruwita et al (2018) find that overall, the lifetime of discs in binaries may not vary significantly compared to disc lifetimes around single stars.…”
Section: Introductionmentioning
confidence: 61%
“…They found that the frequency of close binaries with a < 10 au, detectable by their survey, is compatible with solar-type stars in the field and does not differ substantially between the studied regions. Interestingly, they discovered a deficit of double-lined (largeq) pairs among disc-bearing stars, like those surveyed by Kuruwita et al (2018), that is recovered by the small-q single-lined systems with discs. Rebull et al (2018) also noted that multi-periodic stars in USco (large-q binaries) have a reduced incidence of discs.…”
Section: Discussionmentioning
confidence: 83%
“…No large radial velocity (RV) surveys of USco have been made so far to probe this regime. Kuruwita et al (2018) monitored RVs of 55 disc-bearing members of USco and estimated the frequency of spectroscopic binaries at 0.06 +0.07 −0.02 , like in the field and in other starforming regions (Duchêne & Kraus 2013). Presence of spectroscopic binaries in several northern associations and clusters (not including USco) has been probed by Kounkel et al (2019) using RV measurements from APOGEE.…”
Section: Discussionmentioning
confidence: 99%
“…For a system with a stellar companion external to the circumstellar disc, truncation occurs at 0.3-0.5 times the physical separation of the binary companion (see, for example, Papaloizou & Pringle 1977;Artymowicz & Lubow 1994). 1 A smaller disc also implies a shorter viscous dissipation timescale and previous infrared studies have shown that discs around medium-separation binaries do in fact have shorter lifetimes than those around single stars (Cieza et al 2009;Kuruwita et al 2018). In addition, Rosotti & Clarke (2018) found that secondary components of close binaries clear first due to the shorter viscous time scale associated with the smaller size of the disc, while for wide binaries the difference in photoevaporation rate permits a longer lifetime than tight systems.…”
mentioning
confidence: 99%